A methods engineering study of Suzuki Philippines, Inc. - Chua, Christina S. (College of Engineering, 1996)
This study aims to apply the techniques learned in Methods Engineering to actual production systems in order to improve their productivity. The production system under study is Suzuki, Philippines, Incorporated - a motorcycle manufacturing company. The assembly line section of said company was selected as the focus of the study. The main problem addressed under Work Study is the number of rejects resulting from poor design of bushing press fitting machine and poor materials handling. For the Systems and Procedures part, the activities involving systems and procedures were investigated. The study on Systems and Procedures consist mainly of forms analysis. The recommendations of the team were based on a four point criteria : cost effectiveness, ease of implementation, benefits to management and benefits to worker. The recommendations under Work Study are : provision for adequate support and clamp, introduction of incline to the conveyor rail and provision of a hoist for the transport of engine. The recommendations under Systems and Procedures mainly involved the revision of the contents of the form for clarity and ease of use.